How Collaborative Supply Chains Manage Their Distribution Channels - Acho, Emmanuel (2008)
Globalization, outsourcing, shrinking lifecycles and legislation have all contributed over the past years to the element of risk in supply chain operations. Moreover, global business networks have to be highly responsive to customer needs and ever-changing business environments. In response to these challenges, organizations have been forced to form partnerships in order to guarantee their survival and give them the competitive edge to cut their way through the global competitive landscape. In this light, much has been written on the concept of Supply Chain Collaboration that has been vaunted as a major source of competitive advantage both in literature and practice. But what is Supply Chain Collaboration? How do firms actually collaborate? And what benefits can be gotten from forming such business relationships? This paper tries to answer the above questions from a Logistics Outsourcing point of view. Alongside the collaboration tendency, Logistics has emerged into a key business issue presenting considerable challenges for Supply Chain Management. Moreover, the move away from supply lead supply chains to demand driven supply chains has led many organizations to restructure their distribution channels and channel relationships in order to create more customer value. Answers to the what, why and how of collaboration will be applied to a specific case study that involves a Logistics Outsourcing venture between a global agrochemical manufacturer and a Lead Logistics Service Provider (LLSP). This will enable the subject matter to be situated within a specific context and for subsequent comparisons to be made.